CaPrx, a Coffea arabica gene encoding a putative class III peroxidase induced by root-knot nematode infection - Severino, Fabio E. [UNESP]; Brandalise, Marcos [UNESP]; Costa, Carolina S. [UNESP]; Wilcken, Silvia R. S. [UNESP]; Maluf, Mirian P.; Goncalves, Wallace; Maia, Ivan de Godoy [UNESP] (Elsevier B.V., 2012)
Class III peroxidases (Prxs) are enzymes involved in a multitude of physiological and stress-related processes in plants. Here, we report on the characterization of a putative peroxidase-encoding gene from Coffea arabica (CaPrx) that is expressed in early stages of root-knot nematode (RKN) infection. CaPrx showed enhanced expression in coffee roots inoculated with RKN (at 12 h post-inoculation), but no significant difference in expression was observed between susceptible and resistant plants. Assays using transgenic tobacco plants harboring a promoter-beta-glucuronidase (GUS) fusion revealed that the CaPrx promoter was exclusively active in the galls induced by RKN. In cross sections of galls, GUS staining was predominantly localized in giant cells. Up-regulation of GUS expression in roots of transgenic plants following RKN inoculation was observed within 16 h. Moreover, no increase in GUS expression after treatment with jasmonic acid was detected. Altogether, these results point to a putative role of this peroxidase in the general coffee response to RKN infection. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Coffee; Promoter; Peroxidases; Nematode; Tissue-specificity; Gene expression